Evaluation of ultrasonic parameters as a non-invasive, rapid and in-field indicator of water stress in Citrus plants - Farinas, María Dolores; Martínez-Gimeno, María A.; Badal, Eduardo; Tasa, María; Bonet, Luis; Manzano-Juárez, Juan (Elsevier, 2021)
Non-Contact Resonant Ultrasound Spectroscopy (NC-RUS) has emerged as a powerful tool to determine plant water status in a non-destructive, non-invasive and rapid way. In this study, ultrasonic parameters directly obtained from experimental measurements in the field using NC-RUS - such as resonant frequency (fres), velocity (v) and Q-factor - were evaluated as potential water stress indicators in Citrus plants. The experiments were carried out in two-year-old mandarin trees (Citrus clementina Hort. ex Tan. ‘Clemenules’) grown in pots in an open greenhouse where two different groups of plants were tested: a Control group (full irrigation) and a Drought Stress group (DS) whose irrigation was withdrawn during 7 days, followed by a 16 days recovery period. Soil water content, leaf water potential (Ψleaf) and the considered ultrasonic parameters were measured in the same leaves. fres detected changes between control and DS at day 7 without irrigation. Conversely, v showed differences after day 3, which were statistically significant at day 7, enabling discrimination between C and DS groups. Hence, Q-factor was the ultrasonic parameter that showed statistically significant differences between C and DS groups at days 3 and 7. Consequently, Signal Intensity in Q during the drought treatment showed a similar evolution to Ψleaf, although with slightly lower performance. However, Q-factor sensitivity excels Ψleaf at each day studied. Finally, a linear correlation (R2=0.57) between Ψleaf and Q-factor of all experimental data measured in DS group plants along the drought treatment was found. In conclusion, the ultrasonic parameters obtained using NC-RUS and in particular the Q-factor, demonstrated to be potential new water stress indicators in Citrus trees, with the novelty of being non-destructive, non-invasive and rapid. Future work should explore its suitability for its use in irrigation scheduling for Citrus trees